The 21st-century fate of the Mocho-Choshuenco ice cap in southern Chile - Scheiter, Matthias; Schaefer, Marius; Flandez, Eduardo; Bozkurt, Deniz; Greve, Ralf (Cryosphere, 2021)
Glaciers and ice caps are thinning and retreating along the entire Andes ridge, and drivers of this mass loss vary between the different climate zones. The southern part of the Andes (Wet Andes) has the highest abundance of glaciers in number and size, and a proper understanding of ice dynamics is important to assess their evolution. In this contribution, we apply the ice-sheet model SICOPOLIS (SImulation COde for POLythermal Ice Sheets) to the Mocho-Choshuenco ice cap in the Chilean Lake District (40g g S, 72g g W; Wet Andes) to reproduce its current state and to project its evolution until the end of the 21st century under different global warming scenarios. First, we create a model spin-up using observed surface mass balance data on the south-eastern catchment, extrapolating them to the whole ice cap using an aspect-dependent parameterization. This spin-up is able to reproduce the most important present-day glacier features. Based on the spin-up, we then run the model 80 years into the future, forced by projected surface temperature anomalies from different global climate models under different radiative pathway scenarios to obtain estimates of the ice cap's state by the end of the 21st century. The mean projected ice volume losses are 56±16g % (RCP2.6), 81±6g % (RCP4.5), and 97±2g % (RCP8.5) with respect to the ice volume estimated by radio-echo sounding data from 2013. We estimate the uncertainty of our projections based on the spread of the results when forcing with different global climate models and on the uncertainty associated with the variation of the equilibrium line altitude with temperature change. Considering our results, we project a considerable deglaciation of the Chilean Lake District by the end of the 21st century.
Created from Fastlane, Scopus look-up